Clustered Regularly Interspaced Short Palindromic Repeats/Cas9 Gene Editing Technique in Xenotransplantation - Naeimi Kararoudi, Meisam; Hejazi, Seyyed S.; Elmas, Ezgi; Hellström, Mats; Naeimi Kararoudi, Maryam; Padma, Arvind M.; Lee, Dean; Dolatshad, Hamid (Frontiers in Immunology, 2018)
Genetically modified pigs have been considered favorable resources in xenotransplantation. Microinjection of randomly integrating transgenes into zygotes, somatic cell nuclear transfer, homologous recombination, zinc finger nucleases, transcription activator-like effector nucleases, and most recently, clustered regularly interspaced short palindromic repeats-cas9 (CRISPR/Cas9) are the techniques that have been used to generate these animals. Here, we provide an overview of the CRISPR approaches that have been used to modify genes which are vital in improving xenograft survival rate, including cytidine monophosphate-N-acetylneuraminic acid hydroxylase, B1,4N-acetylgalactosaminyltransferase, isoglobotrihexosylceramide synthase, class I MHC, von Willebrand factor, C3, and porcine endogenous retroviruses. In addition, we will mention the importance of potential candidate genes which could be targeted using CRISPR/Cas9.